Brushing Characteristics and Dietary Patterns of Orthodontic Patients with Fixed Appliances - Shibra Khurshid, Muttayaba Irfan, Naveed Mumtaz, Parsa Salman, Hafiza Asma Jawaid, Maham Munir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Proper brushing practices are required to maintain good oral hygiene. This is of utmost importance in patients with fixed orthodontic appliances as these appliances can facilitate plaque accumulation and make cleaning process difficult. Hence if good oral hygiene is not maintained with these appliances then deterioration of gingival and periodontal health will result. Frequent intake of acidic drinks and sweet food can further harm the teeth. Aim: To determine tooth brushing characteristics of orthodontic patients with fixed appliances. Determine dietary patterns of such patients. Determine other oral hygiene measures used by them. Study Design: Cross sectional study Duration of the study: 6 months Methodology: Questionnaires were conveniently distributed among 104 orthodontic patients who met the inclusion criteria and provided consent to provide the information. Data collected was analyzed using SPSS 2020. Results: Most (70%) of the responding patients brush two times daily. Correct brush type (soft) is in use by 77% of the individuals. Approximately 64-66% of individuals combine vertical and horizontal technique of tooth brushing, use interdental toothbrush and report that they hardly intake fizzy drinks. However, only 55% patients have reported brushing for total duration of 2 minutes. Around 30% of the respondents have frequent intake of junk food and sugary food. Practical Implication: According to our knowledge, this study is the first study to date to evaluate the brushing habits and dietary patterns in Pakistani orthodontic patients with fixed appliances. Conclusions: The present study shows that majority of the patients show good brushing practices but need to improve their total duration of brushing. Frequent intake of junk food, sweets and fizzy drinks are also avoided by most patients. Use of fluoride mouthwashes and floss was seen in lesser proportion of surveyed patients. Keywords: Brushing characteristics, oral hygiene measures, dietary patterns, orthodontic patients with fixed appliances.